A Calcium-Rich Multimineral Intervention to Modulate Colonic Microbial Communities and Metabolomic Profiles in Humans: Results from a 90-Day Trial - Aslam, Muhammad N. (Cancer Prev Res (Phila), 2019)
Aquamin is a calcium-, magnesium-, and multiple trace element–rich natural product with colon polyp prevention efficacy based on preclinical studies. The goal of this study was to determine the effects of Aquamin on colonic microbial community and attendant metabolomic profile. Thirty healthy human participants were enrolled in a 90-day trial in which Aquamin (delivering 800 mg of calcium per day) was compared with calcium alone or placebo. Before and after the intervention, colonic biopsies and stool specimens were obtained. All 30 participants completed the study without serious adverse event or change in liver and renal function markers. Compared with pretreatment values, intervention with Aquamin led to a reduction in total bacterial DNA (P = 0.0001) and a shift in the microbial community measured by thetaYC (θ(YC); P = 0.0087). Treatment with calcium also produced a decline in total bacteria, but smaller than seen with Aquamin, whereas no reduction was observed with placebo in the colon. In parallel with microbial changes, a reduction in total bile acid levels (P = 0.0375) and a slight increase in the level of the short-chain fatty acid (SCFA) acetate in stool specimens (P < 0.0001) from Aquamin-treated participants were noted. No change in bile acids or SCFAs was observed with calcium or placebo. We conclude that Aquamin is safe and tolerable in healthy human participants and may produce beneficial alterations in the colonic microbial community and the attendant metabolomic profile. Because the number of participants was small, the findings should be considered preliminary.